Osnabrück Station to Jerusalem - Cixous, Helene (Book collections on Project MUSE., 2020)
For about eighty years, the Jonas family of Osnabrück were part of a small but vibrant Jewish community in this mid-size city of Lower Saxony. After the war, Osnabrück counted not a single Jew. Most had been deported and murdered in the camps, others emigrated if they could and if they managed to overcome their own inertia. It is this inertia and failure to escape that Helene Cixous seeks to account for in Osnabrück Station to Jerusalem. Vicious anti-Semitism hounded all of Osnabrück's Jews long before the Nazis' rise to power in 1933. So why did people wait to leave when the threat was so patent, so in-their-face? Drawn from the stories told to Cixous by her mother, Ève, and grandmother, Rosalie (Rosi), this literary work reimagines fragments of Ève's and Rosi's stories, including the death of Ève's uncle, Onkel Andre. Piecing together the story of Andreas Jonas from what she was told and from what she envisages, Cixous recounts the tragedy of the one she calls the King Lear of Osnabrück, who followed his daughter to Jerusalem only to be sent away by her and to return to Osnabrück in time to be deported to a death camp. Cixous wanders the streets of the city she had heard about all her life in her mother's and grandmother's stories, digs into its archives, meets city officials, all the while wondering if she should have come. These hesitations and reflections in the present, often voiced in dialogues staged with her own son or daughter, are woven with scenes from her childhood in Algeria and the half-remembered, half-invented stories of the Jonas family, making Osnabrück Station to Jerusalem one of the author's most intensely engaging books.